2020
DOI: 10.1093/asj/sjaa007
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Pattern and Tissue Response to Hyaluronic Acid Gel Injections in the Subcutis: Ultrasound Videos, Ultrasound Measurements, and Histology

Abstract: Background Despite the popularity of hyaluronic acid (HA) filler treatments, few publications focus on their effects on adipose tissue. Objectives The authors assessed the deposition pattern in the subcutis of injected HA, the tissue response at short and intermediate term, and the effects of remodeling the filler by strong finger pressure immediately after the treatment. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…This effect was also sustained throughout the follow-up period. The persistence of the effect of different types of volumiser gels had been previously demonstrated in several other studies [17][18][19][20]. However, an interesting finding in our observations is how fast the volume of the HA gel increased soon after injection.…”
Section: Discussionsupporting
confidence: 80%
“…This effect was also sustained throughout the follow-up period. The persistence of the effect of different types of volumiser gels had been previously demonstrated in several other studies [17][18][19][20]. However, an interesting finding in our observations is how fast the volume of the HA gel increased soon after injection.…”
Section: Discussionsupporting
confidence: 80%
“…Although a minimum frequency of 15 MHz is recommended to study the skin, we found other studies about the sonographic appearance of filler/biostimulators using frequencies lower than 15 MHz. 26,18,27,15 Another limitation is that our study focused on the sonographic aspect of fillers and biostimulators in the buttocks of only one cadaver during and immediately after injection.…”
Section: Discussionmentioning
confidence: 99%
“…The long-lasting effects of HA fillers are still a matter of debate, but several studies have highlighted that these HA gels persist for a longer duration than expected [17,18]. Indeed, HA gels were thought to be reabsorbed within a few months, but several studies suggested that they persist for up to 18 to 24 months [19]. Our study did not include an assessment of persistence.…”
Section: Journal Of Clinical and Cosmetic Dermatologymentioning
confidence: 93%